2018
DOI: 10.3390/s18072299
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Tests of Pellets Made from Manganese Antimonate Nanoparticles in Carbon Monoxide and Propane Atmospheres

Abstract: Nanoparticles of manganese antimonate (MnSb2O6) were prepared using the microwave-assisted colloidal method for its potential application as a gas sensor. For the synthesis of the oxide, manganese nitrate, antimony chloride, ethylenediamine and ethyl alcohol (as a solvent) were used. The precursor material was calcined at 800 °C in air and analyzed by X-ray diffraction. The oxide crystallized into a hexagonal structure with spatial group P321 and cell parameters a = b = 8.8054 Å and c = 4.7229 Å. The microstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 57 publications
2
31
0
Order By: Relevance
“…The optimum temperature depends on the sensing material and the sensed gas. Therefore, as in previous reports [29,43], a noticeable response variation was observed at 300 • C. Comparing our results with references [29,42,43,46], where similar experiments were carried out in static gas atmospheres, we found that our pellets had a greater response and a better performance in detecting CO at different operating temperatures (100-300 • C).…”
Section: Co Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…The optimum temperature depends on the sensing material and the sensed gas. Therefore, as in previous reports [29,43], a noticeable response variation was observed at 300 • C. Comparing our results with references [29,42,43,46], where similar experiments were carried out in static gas atmospheres, we found that our pellets had a greater response and a better performance in detecting CO at different operating temperatures (100-300 • C).…”
Section: Co Analysissupporting
confidence: 89%
“…This resulted in not recording significant increases in the pellets' response at 100 °C (see Figure 8a,b). It is important to mention that the excellent response and good stability recorded at 300 °C were mainly associated with the microstructural features obtained, which led to an increase in catalytic sites for the gas reaction with the nanoparticles' surface [43][44][45].…”
Section: Co Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, the presence of ethylenediamine determines the geometric features of the formed nuclei, which grow during the heat treatments [ 5 ]. We also have reported in previous works that by using ethylenediamine during the synthesis process, it is possible to obtain different types of morphologies [ 5 , 36 , 37 , 38 ], like microrods, nanorods, microspheres, microoctahedra, and nanoparticles, which have been successfully proved as potential gas sensors for the detection of CO, CO 2 , and C 3 H 8 atmospheres [ 39 ]. Additionally, other authors, such as Michel et al [ 40 ], used ethylenediamine for the synthesis of the semiconductor oxide CoSb 2 O 6 in order to obtain nanoparticles to be applied in the detection of CO 2 and O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…This behavior is attributed to the fact that the relatively low-temperature is not enough for the reaction of the pellets’ surface and the test gas. This caused that at 100 °C, oxygen desorption did not occur [ 38 , 39 ] and, therefore, a low response of the material. Some authors also observed the poor response that shows some semiconductors at low temperatures (in our case at 100 °C), such as ours.…”
Section: Resultsmentioning
confidence: 99%